The Importance of Moderately Priced Rental Housing to Continued Economic Growth (Or, Portland’s Rental Housing Plight) - MacLean, Erin (Maine Policy Review, 1999)
Currently, the Greater Portland, Maine area is experiencing a significant shortage in both subsidized rental housing and moderately priced, market-rate rental housing. According to Erin MacLean, the problem is that even with heightened demand, historically low interest rates, and historically high rents, developers are finding that new, market-rate housing is too expensive to build in Portland. The lack of moderately priced housing has affected local business owners as well, who report they are finding it difficult to hire workers in the $8 to $15 range. Their efforts to recruit and retain workers place an upward pressure on wages, which can act as a deterrent to economic growth. In this article, MacLean discusses the circumstances that have led to Portland’s current shortage in rental housing and concludes with a discussion about reducing the costs of construction. She strongly urges local officials to help control costs, and suggests that communities with a clear vision and sensible permitting processes will be more successful in attracting the type of development they desire.
Keywords: Portland Maine; rental housing; affordable housing